2010
DOI: 10.4049/jimmunol.1000434
|View full text |Cite
|
Sign up to set email alerts
|

B Cell Receptor-Mediated Calcium Signaling Is Impaired in B Lymphocytes of Type Ia Patients with Common Variable Immunodeficiency

Abstract: Several lines of evidence have demonstrated B cell intrinsic activation defects in patients with common variable immunodeficiency (CVID). The rapid increase of intracellular free calcium concentrations after engagement of the BCR represents one crucial element in this activation process. The analysis of 53 patients with CVID for BCR-induced calcium flux identified a subgroup of patients with significantly reduced Ca2+ signals in primary B cells. This subgroup strongly corresponded to the class Ia of the Freibu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

7
69
0
1

Year Published

2011
2011
2022
2022

Publication Types

Select...
5

Relationship

4
1

Authors

Journals

citations
Cited by 69 publications
(77 citation statements)
references
References 50 publications
7
69
0
1
Order By: Relevance
“…We further investigated the phenotype of CD21 low CD27 1 B cells, and found that they share with CD21 low CD27 À B cells the expression of a peculiar array of receptors ( Fig. 2) associated with anergy and homing [6,9], thus suggesting similar functional properties.Collectively, our findings are consistent with the concept [5,8] that multiple subsets of B and T cells are dysfunctional in CVID 1a patients. …”
supporting
confidence: 91%
See 4 more Smart Citations
“…We further investigated the phenotype of CD21 low CD27 1 B cells, and found that they share with CD21 low CD27 À B cells the expression of a peculiar array of receptors ( Fig. 2) associated with anergy and homing [6,9], thus suggesting similar functional properties.Collectively, our findings are consistent with the concept [5,8] that multiple subsets of B and T cells are dysfunctional in CVID 1a patients. …”
supporting
confidence: 91%
“…A previous report described overall normal telomeres in T and B cells from CVID patients [21]; however, the mean telomere lengths varied greatly from patient to patient. Since patients were not classified according to the immunophenotype, the data reported in that study appear consistent, rather than contradictory, with distinct subgroups of CVID patients with different rates of telomere attrition.Shortening of telomeres in B cells as well as in T cells of CVID 1a patients is consistent with the notion that both cell types are dysfunctional in this subgroup of CVID [5][6][7][8]. The mean telomere length in whole B-and T-cell populations was independent on the relative predominance of specific subsets such as CD21 low B cells or memory T cells.…”
supporting
confidence: 86%
See 3 more Smart Citations